Chemical profiling and antibacterial screening of crude extracts of soft coral Lobophytum sp. from Straits of Malacca / Tan Yee Yein - Tan , Yee Yein (2021)
Marine natural products have gained popularity in the pharmaceutical field over the years as the ocean is vast and is extraordinarily rich in species diversity, making it the ideal target for exploration. Marine naturals products, isolated from marine sponges, algae and soft corals have been reported to exhibits biological activities such as anti-inflammatory, antitumor, and antimicrobial. In recent years, the emergence of antibiotic resistant bacteria has posed a large threat to healthcare worldwide and new antibacterial compounds are in demand. This study focuses on Lobophytum sp. harvested from The Straits of Malacca, to isolate secondary metabolites and test for antibacterial properties against gram-positive (Staphylococcus aureus and Bacillus subtilis) and gram-negative bacteria (Escherichia coli and Salmonella typhi) using crude extracts. Cholesterol has been isolated and FAME analysis showed the major fatty acid constituents of the sample is palmitic and arachidonic acid, 29.905% and 18.891% respectively. Crude extracts and fractions obtained from column chromatography shows weak inhibition against B. subtilis.